Preparation method and application of tough, anti-freezing and high-conductivity composite hydrogel electrode
By blending acrylamide with nanocellulose and gelatin, and introducing conductive polymer PEDOT:PSS, a composite hydrogel electrode with toughness, frost resistance and high conductivity was prepared, which solved the problem of insufficient conductivity and mechanical properties of existing electrode materials, and achieved high sensitivity and high stability strain sensor applications.
Patent Information
- Application Number
- CN202411899032.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-12-23
AI Technical Summary
The existing composite hydrogel electrodes are difficult to meet the demand for high conductivity, resulting in low signal transmission efficiency and accuracy, which limits their application in high-sensitivity electronic equipment. At the same time, their mechanical properties are not ideal and are prone to rupture or deformation due to external forces, which affects their service life.
A strong, freezing and high conductivity composite hydrogel electrode was prepared by blending acrylamide with nanocellulose and gelatin and introducing the conductive polymer PEDOT:PSS. This method enhances mechanical strength by forming a polyacrylamide network structure and a gelatin-tannin crosslinking structure, and constructs a three-dimensional conductive network through PEDOT:PSS to improve conductivity.
The prepared composite hydrogel electrode has high toughness, frost resistance, antibacteriality, conductivity and biocompatible. It can be used for the preparation of flexible strain sensors, has high sensitivity, high stability and a wide detection range, and is suitable for muscle electrical monitoring, electrocardiogram monitoring or exercise monitoring.
Smart Images

Figure CN119639029A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a preparation method and application of a composite hydrogel electrode, and in particular to a preparation method and application of a composite hydrogel electrode that is strong, frost-resistant and highly conductive. Background Art
[0002] At present, in today's rapidly developing electronic technology field, composite hydrogel electrodes have attracted much attention due to their potential applications in flexible electronic devices, smart wearable devices, biomedical monitoring, etc. These application fields have put forward higher and higher requirements on the performance of electrode materials. For example, in smart wearable devices, electrodes need to have good flexibility and comfort to adapt to the complex movements of different parts of the human body; in biomedical monitoring, electrodes must be compatible with human tissues and ensure the accuracy and stability of signal transmission.
[0003] Hydrogels have many advantages. They have high elasticity and high stretchability, which enables them to adapt to different deformation requirements. They can deform with human body movement without affecting their functions. Good toughness ensures that they will not fail due to repeated deformation during long-term use. Ionic conductivity is adjustable and can be adjusted according to different application scenarios. Its ion transport mechanism is similar to ion transport in organisms, which can improve the accuracy and reliability of flexible sensor measurements in the biomedical field. However, many composite hydrogel electrode materials on the market still have many limitations. Some hydrogel electrodes are prone to failure in complex environments. For example, when exposed to different temperature environments, especially low temperature environments, structural damage and performance degradation may occur, which seriously affects their use in cold areas or in application scenarios that require low temperature storage and transportation. In addition, in terms of conductivity, many existing composite hydrogel electrodes are difficult to meet the requirements of high conductivity, resulting in low efficiency and accuracy of signal transmission, which limits their application in highly sensitive electronic devices. Moreover, the mechanical properties of some electrode materials are not ideal, and they may break or deform due to external forces during use, affecting their overall performance and service life.
[0004] Based on the above problems, the present invention prepares a composite hydrogel electrode by blending acrylamide with nanocellulose and gelatin to improve the mechanical properties of the hydrogel, and improves the conductivity by introducing the conductive polymer PEDOT:PSS. The composite hydrogel electrode has the advantages of high toughness, frost resistance, antibacterial property, conductivity and biocompatibility. It is used to prepare a strain sensor with the characteristics of high sensitivity, high stability and a wide detection range. Summary of the invention
[0005] The main purpose of the present invention is to solve the problem that the existing composite hydrogel electrodes are difficult to meet the requirements of high conductivity, resulting in low efficiency and accuracy of signal transmission, which limits their application in high-sensitivity electronic devices. In addition, the mechanical properties of some electrode materials are not ideal, and they may break or deform due to external forces during use, affecting their overall performance and service life. The present invention provides a method for preparing and using a tough, frost-resistant and highly conductive composite hydrogel electrode.
[0006] The present invention provides a method for preparing a tough, frost-resistant and highly conductive composite hydrogel electrode, the method comprising the following steps:
[0007] Step 1: Add nanocellulose CNF into deionized water, stir rapidly, and disperse it using an ultrasonic device to obtain a uniform dispersed solution, and add dimethyl sulfoxide DMSO into the dispersed solution to obtain a mixed binary solvent;
[0008] Step 2: Add acrylamide AM, gelatin Gel and tannic acid TA powder to the binary solvent prepared in step 1, and stir at room temperature to dissolve them to obtain a uniform and clear precursor solution;
[0009] Step 3, adding the poly(3,4-ethylenedioxythiophene):polystyrenesulfonate PEDOT:PSS solution to the precursor solution prepared in step 2, and rapidly stirring to obtain a mixed solution;
[0010] Step 4: Add N,N'-methylenebisacrylamide MBA and ammonium persulfate APS to the mixed solution prepared in step 3 and stir for 15 minutes to obtain a hydrogel precursor solution. After stirring evenly and ultrasonic defoaming, place it in an oven at 60°C for 4 hours to obtain a strong, frost-resistant and highly conductive hydrogel.
[0011] The concentration of nanocellulose in step 1 is 5 wt %, and the concentration of dimethyl sulfoxide is 35 wt %.
[0012] The concentration of acrylamide in step 2 is 30 wt %, the concentration of gelatin is 0-20 wt % of acrylamide, and the concentration of tannic acid is 0-10 wt % of acrylamide.
[0013] The concentration of the poly(3,4-ethylenedioxythiophene):polystyrenesulfonate PEDOT:PSS solution in step 3 is 2 wt %.
[0014] The dosage of N,N'-methylenebisacrylamide MBA and ammonium persulfate APS in step 4 is 0.1% and 1% of the mass of acrylamide.
[0015] The strong, frost-resistant and highly conductive composite hydrogel electrode prepared by the above method can be used as a strain sensor in muscle electrical monitoring, electrocardiographic monitoring or motion monitoring.
[0016] Beneficial effects of the present invention:
[0017] The present invention provides a tough, frost-resistant and highly conductive composite hydrogel electrode. Under the action of initiator ammonium persulfate (APS), acrylamide forms a polyacrylamide network structure through a crosslinker N,N'-methylenebisacrylamide (MBA). As an overall framework, gelatin molecules are partially crosslinked by tannic acid, and the phenolic hydroxyl groups of tannic acid as hydrogen donors establish abundant hydrogen bonds with the carboxyl and amine groups of gelatin as hydrogen acceptors, and form a double network structure with polyacrylamide. The amino groups of acrylamide form hydrogen bonds with the phenolic hydroxyl groups of tannic acid, thereby enhancing the mechanical strength of the composite hydrogel. At the same time, by introducing PEDOT:PSS, electrostatic interactions can be formed with some charged components in the hydrogel. In addition, the PSS chain can also form a hydrogen bond network with the hydrogel polymer through the sulfonic acid group, thereby constructing a three-dimensional conductive network and enhancing the conductivity of the hydrogel. By introducing DMSO, the high-temperature water retention and low-temperature frost resistance of the hydrogel are improved, and the material stability is good in the temperature range of -40 degrees Celsius to 60 degrees Celsius.
[0018] The present invention uses a strong, freeze-resistant and highly conductive composite hydrogel electrode to assemble into a flexible strain sensor, which has the advantages of high sensitivity, high stability and a wide detection range.
[0019] The preparation method of the present invention is simple and can realize the monitoring of weak physiological signals. The strong, freeze-resistant and highly conductive composite hydrogel electrode provided by the present invention can be used for muscle electricity monitoring, electrocardiogram monitoring or motion monitoring. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 This is a schematic diagram of the preparation method of the composite hydrogel described in the present invention.
[0021] Figure 2 Schematic diagram of stress-strain curves of the samples described in the present invention at different Gel contents.
[0022] Figure 3 It is a schematic diagram of the stress-strain curve of the sample described in the present invention under cyclic stretching under external force.
[0023] Figure 4 This is a schematic diagram of the adhesion strength of the samples described in the present invention to different materials.
[0024] Figure 5 This is a schematic diagram of the resistance change of the sample described in the present invention under different strains.
[0025] Figure 6 Schematic diagram of repeated cyclic resistance change of the sample described in the present invention under the same strain.
[0026] Figure 7 This is a schematic diagram of the sample described in the present invention being used to monitor physiological signals of human muscle electricity.
[0027] Figure 8 This is a schematic diagram of the sample described in the present invention being used to monitor the physiological signals of human electrocardiogram. DETAILED DESCRIPTION
[0028] See also Figures 1 to 8 As shown:
[0029] Embodiment 1:
[0030] The present embodiment provides a method for preparing a tough, freeze-resistant and highly conductive composite hydrogel electrode, the method comprising the following steps:
[0031] Step 1: adding nanocellulose (CNF) into deionized water, stirring rapidly, and dispersing it using an ultrasonic device to obtain a uniform dispersed solution, and adding dimethyl sulfoxide (DMSO) into the dispersed solution to obtain a mixed binary solvent;
[0032] Step 2: adding acrylamide (AM), gelatin (Gel) and tannic acid (TA) powders to the solution prepared in step 1, stirring at room temperature to dissolve them to obtain a uniform and clear precursor solution;
[0033] Step 3, adding poly(3,4-ethylenedioxythiophene):polystyrene sulfonic acid (PEDOT:PSS) solution to the solution prepared in step 2, and rapidly stirring for 5 minutes to obtain a mixed solution;
[0034] Step 4: Add N,N'-methylenebisacrylamide (MBA) and ammonium persulfate (APS) to the mixed solution obtained in step 3 and stir for 15 minutes to obtain a hydrogel precursor solution. After stirring evenly and ultrasonic defoaming, place the solution in an oven at 60°C for 4 hours to obtain a strong, frost-resistant and highly conductive hydrogel.
[0035] In step 1, the concentration of nanocellulose is 5 wt % and the concentration of dimethyl sulfoxide is 35 wt %.
[0036] In step 2, the concentration of acrylamide is 30 wt %, the concentration of gelatin is 5 wt % of acrylamide, and the concentration of tannic acid is 10 wt % of acrylamide.
[0037] In step three, the concentration of poly(3,4-ethylenedioxythiophene):polystyrene sulfonic acid (PEDOT:PSS) is 2wt% and the dosage is 500ul.
[0038] In step 4, the dosage of N,N'-methylenebisacrylamide (MBA) and ammonium persulfate (APS) is 0.1% and 1% of the mass of acrylamide.
[0039] Embodiment 2:
[0040] The present embodiment provides a method for preparing a tough, freeze-resistant and highly conductive composite hydrogel electrode, the method comprising the following steps:
[0041] Step 1: adding nanocellulose (CNF) into deionized water, stirring rapidly, and dispersing it using an ultrasonic device to obtain a uniform dispersed solution, and adding dimethyl sulfoxide (DMSO) into the dispersed solution to obtain a mixed binary solvent;
[0042] Step 2: adding acrylamide (AM), gelatin (Gel) and tannic acid (TA) powders to the solution prepared in step 1, stirring at room temperature to dissolve them to obtain a uniform and clear precursor solution;
[0043] Step 3, adding poly(3,4-ethylenedioxythiophene):polystyrene sulfonic acid (PEDOT:PSS) solution to the solution prepared in step 2, and rapidly stirring for 5 minutes to obtain a mixed solution;
[0044] Step 4: Add N,N'-methylenebisacrylamide (MBA) and ammonium persulfate (APS) to the mixed solution and stir for 15 minutes to obtain a hydrogel precursor solution. After stirring evenly and ultrasonic defoaming, place it in an oven at 60°C for 4 hours to obtain a strong, frost-resistant and highly conductive hydrogel.
[0045] The concentration of nanocellulose in step 1 is 5 wt % and the concentration of dimethyl sulfoxide is 35 wt %.
[0046] The concentration of acrylamide in step 2 is 30 wt %, the concentration of gelatin is 10 wt % of acrylamide, and the concentration of tannic acid is 10 wt % of acrylamide.
[0047] The concentration of poly(3,4-ethylenedioxythiophene):polystyrene sulfonic acid (PEDOT:PSS) in step three is 2wt% and the dosage is 500ul.
[0048] The dosage of N,N'-methylenebisacrylamide (MBA) and ammonium persulfate (APS) in step 4 is 0.1% and 1% of the mass of acrylamide.
[0049] Embodiment 3:
[0050] The method for preparing a tough, frost-resistant and highly conductive composite hydrogel electrode provided in this embodiment comprises the following steps:
[0051] Step 1: adding nanocellulose (CNF) into deionized water, stirring rapidly, and dispersing it using an ultrasonic device to obtain a uniform dispersed solution, and adding dimethyl sulfoxide (DMSO) into the dispersed solution to obtain a mixed binary solvent;
[0052] Step 2: adding acrylamide (AM), gelatin (Gel) and tannic acid (TA) powders to the solution prepared in step 1, stirring at room temperature to dissolve them to obtain a uniform and clear precursor solution;
[0053] Step 3, adding poly(3,4-ethylenedioxythiophene):polystyrene sulfonic acid (PEDOT:PSS) solution to the solution prepared in step 2, and rapidly stirring for 5 minutes to obtain a mixed solution;
[0054] Step 4: Add N,N'-methylenebisacrylamide (MBA) and ammonium persulfate (APS) to the mixed solution obtained in step 3 and stir for 15 minutes to obtain a hydrogel precursor solution. After stirring evenly and ultrasonic defoaming, place the solution in an oven at 60°C for 4 hours to obtain a strong, frost-resistant and highly conductive hydrogel.
[0055] In step 1, the concentration of nanocellulose is 5 wt %, and the concentration of dimethyl sulfoxide is 35 wt %.
[0056] The concentration of acrylamide in step 2 is 30 wt %, the concentration of gelatin is 15 wt % of acrylamide, and the concentration of tannic acid is 10 wt % of acrylamide.
[0057] The concentration of poly(3,4-ethylenedioxythiophene):polystyrene sulfonic acid (PEDOT:PSS) in step three is 2wt% and the dosage is 500ul.
[0058] The dosage of N,N'-methylenebisacrylamide (MBA) and ammonium persulfate (APS) in step 4 is 0.1% and 1% of the mass of acrylamide.
[0059] Embodiment 4:
[0060] The method for preparing a tough, frost-resistant and highly conductive composite hydrogel electrode provided in this embodiment comprises the following steps:
[0061] Step 1: adding nanocellulose (CNF) into deionized water, stirring rapidly, and dispersing it using an ultrasonic device to obtain a uniform dispersed solution, and adding dimethyl sulfoxide (DMSO) into the dispersed solution to obtain a mixed binary solvent;
[0062] Step 2: adding acrylamide (AM), gelatin (Gel) and tannic acid (TA) powders to the solution prepared in step 1, stirring at room temperature to dissolve them to obtain a uniform and clear precursor solution;
[0063] Step 3, adding poly(3,4-ethylenedioxythiophene):polystyrene sulfonic acid (PEDOT:PSS) solution to the solution prepared in step 2, and rapidly stirring for 5 minutes to obtain a mixed solution;
[0064] Step 4: Add N,N'-methylenebisacrylamide (MBA) and ammonium persulfate (APS) to the mixed solution and stir for 15 minutes to obtain a hydrogel precursor solution. After stirring evenly and ultrasonic defoaming, place it in an oven at 60°C for 4 hours to obtain a strong, frost-resistant and highly conductive hydrogel.
[0065] The concentration of nanocellulose in step 1 is 5 wt %, and the concentration of dimethyl sulfoxide is 35 wt %.
[0066] The concentration of acrylamide in step 2 is 30 wt %, the concentration of gelatin is 20 wt % of acrylamide, and the concentration of tannic acid is 10 wt % of acrylamide.
[0067] The concentration of poly(3,4-ethylenedioxythiophene):polystyrene sulfonic acid (PEDOT:PSS) in step three is 2wt% and the dosage is 500ul.
[0068] The dosage of N,N'-methylenebisacrylamide (MBA) and ammonium persulfate (APS) in step 4 is 0.1% and 1% of the mass of acrylamide.
[0069] Comparative Example 1:
[0070] The difference between this comparative example and the above-mentioned embodiment is that: in step 1, dimethyl sulfoxide (DMSO) is not added, that is, the mass of DMSO is 0, and the concentration of tannic acid is 10wt% of acrylamide; in step 2, the concentration of acrylamide is 30wt%, and the concentration of gelatin is 15wt% of acrylamide; in step 3, the concentration of poly(3,4-ethylenedioxythiophene):polystyrene sulfonic acid (PEDOT:PSS) is 2wt%, and the amount is 500ul; in step 4, the amounts of N'-methylenebisacrylamide (MBA) and ammonium persulfate (APS) are 0.1% and 1% of the mass of acrylamide.
[0071] The specific preparation method comprises the following steps:
[0072] Step 1: Add nanocellulose (CNF) into deionized water, stir rapidly, and disperse it using an ultrasonic device to obtain a uniform dispersed solution;
[0073] Step 2: adding acrylamide (AM), gelatin (Gel) and tannic acid (TA) powders to the solution prepared in step 1, stirring at room temperature to dissolve them to obtain a uniform and clear precursor solution;
[0074] Step 3, adding poly(3,4-ethylenedioxythiophene):polystyrene sulfonic acid (PEDOT:PSS) solution to the solution prepared in step 2, and rapidly stirring for 5 minutes to obtain a mixed solution;
[0075] Step 4: Add N,N'-methylenebisacrylamide (MBA) and ammonium persulfate (APS) to the mixed solution and stir for 15 minutes to obtain a hydrogel precursor solution. After stirring evenly and ultrasonic defoaming, place the solution in an oven at 60°C for 4 hours to obtain a hydrogel.
[0076] Comparative Example 2:
[0077] The difference between this comparative example and the above embodiment is that: in step 1, the concentration of nanocellulose is 5wt%, the concentration of dimethyl sulfoxide is 35wt%, in step 2, the concentration of acrylamide is 30wt%, the concentration of gelatin is 15wt% of acrylamide, and tannic acid (TA) is not added, that is, the mass of TA is 0; in step 3, the concentration of poly (3,4-ethylenedioxythiophene): polystyrene sulfonic acid (PEDOT:PSS) is 2wt%, and the amount is 500ul; in step 4, the amounts of N,N'-methylenebisacrylamide (MBA) and ammonium persulfate (APS) are 0.1% and 1% of the mass of acrylamide.
[0078] The specific preparation method comprises the following steps:
[0079] Step 1: adding nanocellulose (CNF) into deionized water, stirring rapidly, and dispersing it using an ultrasonic device to obtain a uniform dispersed solution, and adding dimethyl sulfoxide (DMSO) into the dispersed solution to obtain a mixed binary solvent;
[0080] Step 2: Add acrylamide (AM) and gelatin (Gel) powder to the solution prepared in step 1, and stir at room temperature to dissolve them to obtain a uniform and clear precursor solution;
[0081] Step 3, adding poly(3,4-ethylenedioxythiophene):polystyrene sulfonic acid (PEDOT:PSS) solution to the solution prepared in step 2, and rapidly stirring for 5 minutes to obtain a mixed solution;
[0082] Step 4: Add N,N'-methylenebisacrylamide (MBA) and ammonium persulfate (APS) to the mixed solution prepared in step 3 and stir for 15 minutes to obtain a hydrogel precursor solution. After stirring evenly and ultrasonic defoaming, place the solution in an oven at 60°C for 4 hours to obtain a hydrogel.
[0083] Test method:
[0084] The mechanical properties, adhesion properties and conductivity properties of the conductive hydrogel materials prepared in the examples and comparative examples were tested.
[0085] The specific test method for tensile properties test is as follows:
[0086] The mechanical properties of the hydrogel samples were evaluated using a universal testing machine. The tensile test was performed on dumbbell-shaped samples with a test size of 20×10×2 mm at a constant speed of 100 mm / min. Each experiment was repeated five times and the average results were recorded.
[0087] The specific test method for compression performance test is as follows:
[0088] The compression test was conducted on a cylindrical sample with a diameter of 10 mm and a height of 10 mm at a constant speed of 10 mm / min. Each experiment was repeated five times and the average result was recorded.
[0089] The specific test method for the adhesion performance test is as follows: Using a universal electronic testing machine, the lap shear test is used to calculate the adhesion ability of the hydrogel, with a size of 10×10×2mm 3 The hydrogel pattern is fitted on two pieces of 20×40×3mm 3 The substrates were pressed with a 500 g weight for 1 minute to achieve close contact.
[0090] Next, a tensile test was performed at a constant speed of 10 mm / min to obtain the adhesion strength of the sample.
[0091] The specific test method of the sensing performance test is as follows: different stretching lengths are set on a universal testing machine connected to a digital source instrument to test the strain sensitivity of the hydrogel sensor under different stretching strains. The flexible sensor is attached to different motion joints of the human body to monitor different movements, such as fingers, elbows, knees, etc. The real-time resistance changes under different motion states are recorded in real time through a computer control interface, and the results are analyzed and calculated. The human muscle electricity and electrocardiogram are recorded at the arm muscle and wrist positions by connecting electrodes.
[0092] The test results are shown in the table below.
[0093]
[0094] As can be seen from the accompanying drawings, the hydrogel prepared by the present invention is a strong, highly conductive composite hydrogel and can be used as a strain sensor for sensing monitoring.
[0095] Therefore, compared with the prior art, the method for preparing the tough, frost-resistant and highly conductive composite hydrogel electrode provided by the present invention can obtain a product with better working ability, and can greatly shorten the preparation steps and improve work efficiency.
Claims
1. A method for preparing a tough, frost-resistant and highly conductive composite hydrogel electrode, characterized in that: The method comprises the following steps: Step 1: Add nanocellulose CNF into deionized water, stir rapidly, and disperse it using an ultrasonic device to obtain a uniform dispersed solution, and add dimethyl sulfoxide DMSO into the dispersed solution to obtain a mixed binary solvent; Step 2: Add acrylamide AM, gelatin Gel and tannic acid TA powder to the binary solvent prepared in step 1, and stir at room temperature to dissolve them to obtain a uniform and clear precursor solution; Step 3, adding the poly(3,4-ethylenedioxythiophene):polystyrenesulfonate PEDOT:PSS solution to the precursor solution prepared in step 2, and rapidly stirring to obtain a mixed solution; Step 4: Add N,N'-methylenebisacrylamide MBA and ammonium persulfate APS to the mixed solution prepared in step 3 and stir for 15 minutes to obtain a hydrogel precursor solution. After stirring evenly and ultrasonic defoaming, place it in an oven at 60°C for 4 hours to obtain a strong, frost-resistant and highly conductive hydrogel.
2. The method for preparing a tough, frost-resistant and highly conductive composite hydrogel electrode according to claim 1, characterized in that: The concentration of nanocellulose in step 1 is 5 wt %, and the concentration of dimethyl sulfoxide is 35 wt %.
3. The method for preparing a tough, frost-resistant and highly conductive composite hydrogel electrode according to claim 1, characterized in that: The concentration of acrylamide in step 2 is 30wt%, the concentration of gelatin is 0-20wt% of acrylamide, and the concentration of tannic acid is 0-10wt% of acrylamide.
4. The method for preparing a tough, frost-resistant and highly conductive composite hydrogel electrode according to claim 1, characterized in that: The concentration of the poly(3,4-ethylenedioxythiophene):polystyrenesulfonate PEDOT:PSS solution in step 3 is 2 wt %.
5. The method for preparing a tough, frost-resistant and highly conductive composite hydrogel electrode according to claim 1, characterized in that: The dosage of N,N'-methylenebisacrylamide MBA and ammonium persulfate APS in step 4 is 0.1% and 1% of the mass of acrylamide.
6. The strong, frost-resistant and highly conductive composite hydrogel electrode prepared by the preparation method of a strong, frost-resistant and highly conductive composite hydrogel electrode according to claim 1 can be used as a strain sensor in muscle electrical monitoring, electrocardiogram monitoring or motion monitoring.
Citation Information
Patent Citations
Polyacrylamide-nanocellulose crystal-silver nanoparticle composite conductive anti-freezing organic hydrogel as well as preparation method and application thereof
CN113248730A
Conductive polymer hydrogel sensing material with high elongation and strain sensitivity as well as preparation method and application of conductive polymer hydrogel sensing material
CN114044920A
Preparation method of hydrogel composite material
CN116535683A
High-tensile adhesive sodium alginate / polyacrylamide / tannic acid hydrogel as well as preparation method and application thereof
CN117843995A
Polyacrylamide-polyvinyl alcohol-MXene-PEDOT: PSS composite conductive organic hydrogel and application thereof
CN118063801A
Cited By
Lithium battery pole piece processing method and lithium battery preparation method thereof
CN120784288A